Antibacterial and Cytotoxicity Activities of Major Compounds from Tinospora cordifolia Willd. Growing on Mangifera indica L. - Taechowisan Thongchai (International Journal of Nutrition, 2019)
Objective To investigate the major constituents of Tinosporacordifolia Willd. growing on Mangiferaindica, and to evaluate the efficacy of their antibacterial and cytotoxicity activities. Methods The ethanolic stem extract of T. cordifolia was subjected to silica gel 60 column chromatography, thin layer chromatography and medium pressure liquid chromatography for isolation of the major compounds. Identification of purified compounds was achieved by spectroscopic methods.. The crude extract and purified compounds were screened for their antibacterial and cytotoxicity properties using standard procedures. Results Two alkaloids were purified and identified as Magnoflorin (1) and Tembetarine (2). These compounds showed high antibacterial activity against Bacillus cereus and Staphylococcus aureus with both MIC (32-64 µg/ml) and MBC (128-256 µg/ml). The cytotoxicity activity of the purified compounds and crude extract was determined using MTT colorimetric assay against L929 and HEK293 cell lines. This showed weak cytotoxicity activity with IC50 values of 1162.24 to 2290.00 µg/ml and 1376.67 to 2585.06 µg/ml towards L929 and HEK293 cell lines, respectively. Conclusion The major compounds present in ethanolic stem extract of T. cordifolia growing on M. indica were extracted, purified and identified. This study suggests that these compounds exhibit great potential for antibacterial activity with weak cytotoxicity activity. They may be useful for their medicinal functions.
Keywords: antibacterial activity